May titanium spiral tacks contribute to intra-abdominal adhesion formation? - Goldenberg,Alberto (2012)
PURPOSE: To verify if titanium spiral tacks may contribute to intra-abdominal adhesion formation in rabbits. METHODS: Ten New Zealand white rabbits were used. Through videolaparoscopic surgery two titanium spiral tacks (ProTack®, Covidien®) were applied in the right flank. After 30 days the animals were submitted to evaluate peritoneal cavity by videolaparoscopy. RESULTS: No adhesion was found where the titanium spiral tacks were placed. CONCLUSION: Titanium spiral tacks for fixation do not cause adhesions in rabbits.